The effect of sample size on the microstructure and mechanical properties of Ti2448 (Ti-24Nb-4Zr-8Sn wt%). (1st January 2023) - Church, NL; Connor, LD; Jones, NG
Abstract: Ti-Nb based alloys are of commercial importance due to their damping capabilities via a superelastic transformation. However, the starting microstructure of these alloys is often not consistent between studies, even when produced via a nominally comparable methodology, which has the potential to limit the reversibility of the transformation. As such, samples were produced to investigate whether the thickness of the material influenced the microstructures and behaviours seen. It was shown that a single-phase layer exists close to the surface of a two-phase microstructure, and that in very thin material, this can span across the whole sample, promoting more recoverable transformation behaviour. This is important as it not only rationalises discrepancies in the literature, but may also influence component geometries necessary for industrial application. Graphical abstract: Image, graphical abstract